Designing an Integrated Learning Action Plan to Build Strategic Learning Environments - Netaniel Giovanni; Martha Monica Olivia Pangaribuan; Deddy Candra (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2024)
This study explores an integrated instructional design framework by combining the ADDIE model, Dick and Carey’s systematic instructional phases, and Backward Design, aiming to bridge skill gaps and address organizational challenges within government agencies, specifically BDKPKU. The research focuses on creating strategic learning environments that enhance cognitive and affective outcomes while aligning competency development with financial accountability goals. Key dimensions evaluated include satisfaction, cognitive impact, instructional design, leadership, and learner orientation. Using a mixed-methods approach, the study incorporated pretests, posttests, and problem-solving action learning, revealing substantial improvements in participants' comprehension and practical application of concepts. The implementation emphasized self-regulated, collaborative, experiential learning activities tailored to real-world scenarios. Results showed significant increases in engagement, motivation, and collaboration, confirming the efficacy of the integrated learning model in fostering critical skills. The research underscores the importance of leadership commitment and adaptive scheduling in sustaining learning outcomes. This model offers a replicable framework for competency development across government agencies by aligning training objectives with organizational needs. Future applications could extend the model’s principles to address broader educational and organizational challenges, ensuring a sustainable impact on workforce performance and policy implementation. This approach emphasizes meaningful learning experiences, integrating theoretical knowledge with practical applications to achieve long-term professional growth.